The olfactory receptor OR51E2 activates ERK1/2 through the Golgi-localized Gβγ-PI3Kγ-ARF1 pathway in prostate cancer cells - Xin Xu; Mostafa Khater; Guangyu Wu (Frontiers Media S.A., 2022)
The olfactory receptor OR51E2 is ectopically expressed in prostate tissues and regulates prostate cancer progression, but its function and regulation in oncogenic mitogen-activate protein kinase (MAPK) activation are poorly defined. Here we demonstrate that β-ionone, an OR51E2 agonist, dose-dependently activates extracellular signal-regulated kinases 1 and 2 (ERK1/2) in prostate cancer cells, with an EC50 value of approximate 20 μM and an efficiency comparable to other receptor agonists. We also find that CRISPR-Cas9-mediated knockout of Golgi-translocating Gγ9 subunit, phosphoinositide 3-kinase γ (PI3Kγ) and the small GTPase ADP-ribosylation factor 1 (ARF1), as well as pharmacological inhibition of Gβγ, PI3Kγ and Golgi-localized ARF1, each abolishes ERK1/2 activation by β-ionone. We further show that β-ionone significantly promotes ARF1 translocation to the Golgi and activates ARF1 that can be inhibited by Gγ9 and PI3Kγ depletion. Collectively, our data demonstrate that OR51E2 activates ERK1/2 through the Gβγ-PI3Kγ-ARF1 pathway that occurs spatially at the Golgi, and also provide important insights into MAPK hyper-activation in prostate cancer.